Impact of Leadership on Sales Performance Mediated by Digital Intellectuality and Innovation in Aceh Province, Indonesia - ., Adnan; Abubakar, Rusydi; ., Suryani; ., Keysha (Journal of Ecohumanism, 2024)
This study investigates how transformational and adaptive leadership influence sales performance in retail stores in Aceh Province, Indonesia, with digital intellectuality as a mediator and technological innovation as a moderator. Primary data were collected via a questionnaire distributed to 300 owners and employees of minimarkets, grocery stores, and cafes in North Aceh Regency, Bireuen Regency, and Lhokseumawe City. Using Structural Equation Modeling with Partial Least Squares (SEM-PLS) for analysis, the findings reveal that both leadership styles positively impact digital intellectuality, which enhances technological innovation and boosts sales performance. Transformational leadership significantly mediates the relationship between digital intellectuality and sales performance, while adaptive leadership indirectly influences sales performance through digital intellectuality and technological innovation, highlighting the critical role of leadership in optimizing sales outcomes.